GEORGIA: ONFLICT REGIONS AND THE ECONOMY - GOTSIRIDZE, Roman (CENTRAL ASIA AND THE CAUCASUS, 2004)
The conflicts in Abkhazia and South Ossetia have been of considerable detriment to Georgia and perceptibly reduced its economic potential. The current situation has directly or indirectly given rise to the following problems: the economic borders of the state and domestic market are un-protected, smuggling and criminalization of business are growing, there is a high level of shadow transactions in the economy and corruption, there is a severe financial and budget crisis caused by low tax collection and a growing balance of trade deficit, there is drop in investments and leak in capital, the foreign debt is increasing, production has undergone a severe slump, and financial and material resources are being allocated from the state budget, which is limping anyway, to resolve the social problems of refugees and forced mi-grants. To these problems should also be added the extreme poverty of the refugees, their homeless-ness, the unbearable living conditions in temporary shelters and the threat of political destabilization caused by this threat, the decline in the size of the population (depopulation) due to emigration and the sharp drop in the fertility rate, and the rise in crime (including among refugees, most of whom are unemployed). These conflicts are particularly prevalent in the border regions. The main land routes connecting Georgia with Russia and other European countries pass through their territory.